PROCEDURE FOR EXPORTING IMPORTED POST DELIVERY GOODS AT THE HANGGAR OF THE KPPBS TMP B OFFICE IN PALEMBANG - YIKE DIANA PUTRI; Sri Porwani; AGUNG INDRIANSYAH (Jurnal Ekonomi, 2022)
To analyze the procedure for releasing imports of postal goods at the Post Office Hangar KPPBC TMP B Palembang, using descriptive analysis by going directly to the field and collecting the necessary data and then processing it. The results achieved from an analysis are useful for improving or improving services both from the Post Office and Customs and Excise for the wider community. In conclusion, the procedure for releasing imports of postal goods at the Post Office Hangar KPPBC TMP B Palembang is not only carried out by Post Office Officers, but also involves Customs and Excise Officers. Therefore, it is necessary to clarify the flow in the issuance of imported postal goods and it is necessary to hold more socialization to the wider community.